Surgical Anatomy of the Distal Part of the Dorsal Scapular Nerve With a Focus on the Triple‐Tendon Transfer - Beyza Celikgun; Ozcan Gayretli; Ilke Ali Gurses; Osman Coskun; Aysin Kale (Brain and Behavior)
ABSTRACT Introduction A review of the literature shows that most studies of the dorsal scapular nerve (DSN) have focused on morphological evaluation of the proximal part of the nerve. Morphometric studies contributing to clinical applications are limited. Therefore, we aimed to investigate the topographic and morphometric anatomy of the distal part of the DSN. Methods 13 cadavers in the Department of Anatomy, Istanbul Faculty of Medicine, were examined bilaterally. DSN dissection was performed on the anterior surface of the levator scapulae and rhomboids, and the distance to the medial border of the scapula (MBS) was recorded at different levels. The insertion lengths of the levator scapulae and rhomboids were also measured. Results Two types of DSN were observed according to the level of termination in the muscle. Contrary to its classical course, the nerve ran laterally to the MBS on the four sides. The shortest distance between the nerve and the MBS was at the level of the superior border of the rhomboid minor (4.46 ± 9.88 mm). The insertion lengths of the levator scapulae and rhomboids according to gender and the insertion length of the rhomboid minor according to the level of termination in the muscle were significant. Discussion We have obtained results that may be useful during Eden–Lange tendon transfer. The DSN is not always located medial to the MBS, it may be located lateral to it. To avoid nerve damage, we believe it is important to identify the nerve on the anterior surface of the muscles for a successful surgery.